MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS II SD - Ida Agustini; Sandha Soemantri; Sayyidati Marlinda Yunita (Universitas Muhammadiyah Surabaya, 2024)
This research was conducted with the aim of improving student learning outcomes. This research uses a classroom action research (PTK) and quantitative descriptive model. This PTK step consists of 2 cycles. Each cycle is completed in time. The research subjects are class II students in the first semester of the 2023/2024 academic year. The instruments applied in the activity are written tests, documentation and observation, while the evaluation focuses on the process, results and outcomes. test and non-test based. The results of the research show that the use of STAD type cooperatives is able to improve students' abilities. This can be seen in the sharp increase in Indonesian language scores, cycle I (number 2080, average of 77, absorption capacity of 70%, learning completeness of 70%) and cycle II (number 2650, average 98, absorption capacity 903%, learning completeness 93%). There was an increase in learning outcomes between cycle I and cycle II, showing an average increase in absorption capacity of 8% and learning completion an increase of 23%. Conclusion: The implementation of STAD type cooperatives in class 2 students at SD Negeri Kertajaya v/ 211 semester I of the 2023/2024 academic year can improve Indonesian language learning outcomes